Features learning content management system intellectual property in the european research area - Fesenko, N. S. (Problems of Engineer-Pedagogical Education, 2018)
The article examines the main prerogatives of the modern development of the states – economic prosperity, security of existence, information and communication space and freedom of movement of knowledge and intellectual achievements. The results of intellectual activity are determined as a driver of socio-economic development of any country. The paper presents the principles of the ranking of countries according to the degree of the world economic condition, including the definition of the index of global competitiveness, the availability of new technologies and scientific inventions. The system of distribution of states into groups in the world ranking is analyzed, where the first – it is the country's «infancy», which ensure the competitiveness within the existing natural resources and cheap unskilled labor; the second – it is the countries of «effective development», that means to the presence in their markets complex and technologically high-quality products; the third – countries «stage of innovative development», where there are the unique and exclusive products of high quality and complexity, so that business can compete in global markets. The features of a common European policy in the field of scientific research and intellectual property are determined, which are the main driver of European competitiveness in a globalizing world. The prerogatives of the functioning of the European Research Area are exposed, which generalizes the European way to the excellence in the scientific research and protection of intellectual product. The necessity of introduction of European experience of the supporting scientific, innovation and intellectual activity in Ukraine is proved.